A model for change management - Kramer, J.; Magee, J. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
The requirements needed to manage arbitrary changes to a system configuration are analyzed, and a model which separates application concerns from those at the configuration level is presented. This permits the formulation of general structural rules for change without the need to consider application state, as well as the specification of application actions without knowledge of the actual changes which might be introduced. The changes can be affected in such a way as to leave the modified system in a consistent state and cause minimal disturbance to the application during change. The model is applied to an example problem, the 'evolving philosophers' problem. The principles described in this model have been implemented and tested in the Conic environment for distributed systems.< >